Strategies used by farmers to cope with drought in Machakos County, Kenya - Thiongo, Karuri; Ngaira, Professor Josephine . K. W; china, Professor S (IJRDO - Journal of Applied Management Science, 2016)
Drought is defined as a prolonged and abnormally dry and hot period which causes a scarcity of water for the normal needs of the affected community and ecosystem. It is a slow onset disaster that is believed to be the primary cause of famine due to crop failure. Droughts present a serious threat to local, national and global development. In Kenya drought affects more than three-quarters of land which is arid and semi-arid. The effects of drought include; death of animals, loss of human lives, cases of malnutrition, crop failure, and famine and water scarcity. To mitigate these effects, farmers have developed various strategies which are both indigenous and modern. Such strategies include: the provision of relief food, out-migrations, destocking-restocking, remittances and donation, market exchanges, and the provision of savings and credit facilities. However, the extent and nature of these coping strategies have not been researched. The study was conducted in Machakos County where farmers experience all types of drought and the listed strategies are used. The overall objective of the study was to investigate farmers coping strategies to drought and their implications to agricultural production. Specific objectives of the study were: to establish socio-economic characteristics of the farmers and types of farming practiced in the study area; to establish farmers knowledge of drought and causes of drought in the study area; to evaluate drought coping strategies used by farmers in response to drought in the study area and to examine the effect of drought coping strategies on farm production in the study area. Both qualitative and quantitative data were collected using questionnaires. These included farmers’ views on whether; drought had been noticed, temperature had increased, length of seasons had changed, rainfall had decreased; and frequency of drought, coping strategies and their effects on production. Mixed research design was employed in this study. Study population included 350 small-scale farmers randomly sampled in all the 8 sub-Counties. Collection of data was done by interviewer guided questionnaires and Focus group discussion guides and interview schedules. Data were analyzed using frequencies, percentages, score ranking and presented through cross tabulations, pie charts, tables and discussions. The major findings included: the mean household farm size being 3.05 acres. Thirty four percent (34%) earned between 6001 and 20000, 23% earned between 3001 and 4500, 18% earned 1501- 3000, 15% earned 4501-6000 and 3% of the respondents earned 20001 and above, Ninety nine percent (99%) of respondents were affected by drought and Eighty-six percent (86%) of respondents observed a change in the timing of rainfall. Almost half of the farmers (48%) defined drought as shortage of rain during the rainy season and twenty percent (20%) as cessation of rain during the rainy season. Ninety two 92(%) percent of the respondents attributed planting cassava to improved farm production and 19% (69 farmers) recommended planting of drought resistant variety of crops. Seventy one percent (71%) said that multicropping increased farm production to a large extent. There is therefore a positive relationship between the strategies used by farmers and farm production. The findings of the study are useful to agricultural policy makers, government agencies dealing with drought, organizations working in drought prone areas in their search for solutions to drought impacts in Kenya.